Expression, purification and biochemical characterization of GumI, a monotopic membrane GDP-mannose:glycolipid 4-{beta}-D-mannosyltransferase from Xanthomonas campestris pv. campestris - Salinas, Silvina Rosa (2011)
We describe the first biochemical characterization of the gumI gene product, an essential protein for xanthan polysaccharide synthesis. Cellular fractionation experiments reveal the presence of a protein associated with the membrane fraction, even in the absence of the other proteins responsible for the synthesis of glycolipid intermediates and the proteins involved in the polymerization and transport of the xanthan chains. By alkaline buffer extraction and detergent phase partitioning, GumI was categorized as a monotopic membrane protein. GumI was overexpressed in Escherichia coli, solubilized and purified in an active and stable form using a simple and reproducible two-step procedure. The purified recombinant GumI is a nonprocessive β-mannosyltransferase that uses GDP-Man as a donor substrate and glucuronic acid-β-1,2-mannose-α-1,3-glucose-β-1,4-glucose-PP-polyisoprenyl as an acceptor. We also established the optimal biochemical conditions for GumI enzymatic activity. Sequence analysis revealed the presence of a conserved domain for glycosyltransferases (GTs) of the GT-B superfamily and homologous proteins in several prokaryote organisms. On the basis of this biochemical characterization, GumI may represent the founding member of a new GT family in the Carbohydrate-Active EnZymes classification.